Persaingan Usaha bagi Muslim yang Berprofesi Penjual Kopi (Studi Kasus di Desa Sumberwudi Kec. Karanggeneng Kab. Lamongan dengan Perspektif Ekonomi Syariah dan Perspektif Sosiologis) - Mutafarida, Binti; Fahmi, Moh. Farih; Mahardini, Hilmiyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This article discusses Muslims who work as coffee shop sellers and how to conduct business competition. So in this article I will try to discuss the first about the reasons behind the coffee shop that apply different business competition methods as in general. Second, we want to examine the problem of different business competition methods based on the sharia economic approach, and the third is a different business competition method based on a sociological approach. The methodology used is to use a case study approach and a social-economics approach. The results of this study are that there are three reasons why this can occur: the first is religiosity, the second is reading market share, and the third is habit. From these three reasons when viewed from the perspective of Islamic economics is in accordance with the teachings of the Qur'an and Hadith. Also in the sociological point of view with his social theory pieree breau breuu. So that in general the coffee shop in Sumberwudi village can be concluded to have its own style in business competition, although there is a homogeneous and zero competition impression